Hypolimnetic oxygenation 3: an engineered switch from eutrophic to a meso-/oligotrophic state in a California reservoir. (3rd July 2019) - Horne, Alex J.; Beutel, Marc
Abstract: Horne AJ, Beutel M. 2019. Hypolimnetic oxygenation 3: an engineered switch from eutrophic to a meso-/oligotrophic state in a California reservoir. Lake Reserv Manage. 35:338–353. A long-term improvement in water quality due to a hypolimnetic oxygenation system (HOS) used without other management actions was shown for Camanche Reservoir in California (volume = 514 million m 3 ). Prior to oxygenation, the reservoir was eutrophic with low water clarity, high chlorophyll a (Chl- a ), and blooms of cyanobacteria primarily caused by internal nutrient loading from anoxic sediments. All 4 trophic state indicators showed major improvement, most pointing to a new oligotrophic state. Days after HOS startup in July 1993, hypolimnion soluble phosphate and ammonium concentrations declined and, unexpectedly, nitrate remained low. This report covers pre-HOS (1988 to mid-1993) and 12 yr of post-HOS measurements (mid-1993 to mid-2005). For surface waters during the growth season (Apr–Oct) after HOS, average Chl- a decreased 79% (14.6–3.1 μg/L) and peak Chl- a decreased sixfold (from 49 to 8 μg/L). Average Secchi depth increased 10-fold (0.47 to 4.9 m) and peak Secchi depth doubled (4.2–8 m). Cyanobacteria ( Aphanizomenon and Dolichospermum, formerly Anabaena ) decreased >95% while the previously absent Merismopedia, an indicator of clean water, appeared. The large colonial diatom Fragilaria also decreased by >90%. Zooplankton (rotifers and crustaceans) appeared unchanged. After HOS, late winter surface nutrients prior to the next spring bloom were much reduced (total phosphorus, TP, by 58%, total inorganic nitrogen, TIN, by 88%). The TIN:TP ratio dropped from 6 to 1.6. In 2004, the last full year of measurements, further declines were found for nitrate nitrogen (42–3 μg/L) and Chl- a (3.1–2.8 μg/L) while TP was unchanged (14 μg/L).